Study on the Characteristics of Crystal Formation and Transformation of Alkali-Activated Slag Minerals Induced by Weak Alkali - Guodong Huang; Yonghao Huang; Xiaojun Zheng; Fengan Zhang; Jiahao Xu; Jun Qi; Zijian Chen (Crystals)
Strong-alkali activation is a prerequisite needed to ensure the full polymerization activity of alkali slag binder and establish excellent mechanical properties; however, it substantially increases the preparation cost. In this study, the effects of both strong and weak alkaline activators on the activation performance of alkali slag were examined, using a combination of X-ray diffraction, scanning electron microscopy, and Fourier-transform infrared spectroscopy analysis methods. The reaction mechanism was analyzed under different alkaline conditions, and the preparation cost could be significantly reduced without significantly degrading mechanical properties. The results indicate that Ca(OH)2 can stimulate the reactivity of slag, resulting in a 40% decrease in compressive strength (compared to NaOH) but a 25–50% reduction in preparation cost. With increasing Ca(OH)2 dosage, the compressive strength first increases and then decreases. The best excitation effect is achieved at a dosage of 40 g Ca(OH)2 per 450 g GBFS. The formation of aluminosilicate is the main driving force for the observed increase in compressive strength. Excessive dosage of Ca(OH)2 will lead to its deposition in the specimen, thus affecting the development of compressive strength.